Pertussis burden and acellular pertussis vaccine effectiveness in high risk children. Issue 9 (23rd February 2022) - Sheridan, Sarah; McIntyre, Peter; Liu, Bette; Fathima, Parveen; Snelling, Thomas; Blyth, Christopher; Klerk, Nicholas de; Moore, Hannah; Gidding, Heather; ,
Abstract: Background: Pertussis hospitalisation is more common among infants born prematurely, who have significant comorbidities, or are Indigenous, but acellular pertussis (aP) vaccine effectiveness (VE) estimates in these sub-groups are lacking. We measured aP VE by Indigenous status, and policy-relevant categories of prematurity and comorbidity, in a population-based Australian cohort. Methods: Perinatal, disease notification, hospitalisation, mortality, and vaccination data were linked to birth records in two Australian states (Western Australia and New South Wales) 2001–2012, with follow-up to the end of 2013. Children followed to 18 months of age were stratified by Aboriginality, prematurity (<32 vs 32–<37 weeks gestation) and comorbidities identified from hospital discharge coding. Rates, rate ratios and VE were calculated for first episode of hospitalised and non-hospitalised pertussis notifications using adjusted Cox proportional hazards models. Results: Among >1, 300, 000 children, 63, 867 (4·9%) were Aboriginal, 47, 721 (3·6%) had at least one comorbidity and 3, 771 first episodes of notified pertussis occurred <18 months of age; of these, 1, 207 (32.0%) had an associated pertussis-coded hospitalisation. For hospitalised pertussis in Aboriginal and non-Aboriginal children, there was significant protection post dose 1 (VE 51% v 25%), 2 (VE 69% v 74%) and 3 (VE 76% v 80%). For children with co-morbidities, VE for hospitalised pertussis was low and non-significant post dose 1 (0%) and 2 (30%). Post dose 3, VE was significant for hospitalised pertussis (70%; 95% CI 29–87) but not for non-hospitalised pertussis (24%; 95% CI −49 to 61). Conclusions: For most Aboriginal and non-Aboriginal children, improved timeliness of current infant doses and higher antenatal coverage should further improve protection against pertussis of any severity. For children at highest risk of severe pertussis (born <32 weeks gestation or with significant medical comorbidities), our data suggest that additional measures-such as extra doses of pertussis-containing vaccines and/or vaccines with improved immunogenicity–are needed for protection.